Microneurosurgical aspects in the management of posterior cranial fossa epidermoids: experience of 24 cases - Chandra, V. V. Ramesh; Prasad, B. C. M.; Niranjan, V.; Rajesh, Paradesi (International Journal of Research in Medical Sciences, 2020)
Background: There is considerable debate in the surgical management of epidermoid cyst, whether gross total or subtotal resection yields better long term outcomes. We present our institutional experience in evaluating the clinical presentation, diagnosis, and surgical strategy and extent of resection in the management of posterior cranial fossa epidermoid cyst. Methods: A retrospective review of 24 patients diagnosed with posterior cranial fossa epidermoid tumors surgically treated at the institution between January 2010 and July 2019. Results: A total of 24 patients who underwent surgery for intracranial epidermoid lesions were identified. Of these 13 were in the Cerebellopontine angle region, eight were in the fourth ventricle, and three in lateral cerebellar convexity. The mean duration from onset of symptoms to surgery was 1.6 years. Cranial nerve dysfunction was noted in 73% of patients preoperatively, most of them being the CPA epidermoids. Total removal was achieved in 16 patients, near-total resection in 6 patients, and subtotal removal in 2 patients. Three patients developed recurrence radiologically of them only one patient became symptomatic. The mean duration of follow-up was 3.8 years. The content of the tumor was pearly white material in all cases. Complications noted in the present series were not related to the completeness of excision. Mortality was noted in one patient. Conclusions: The present study highlights various precautions to be taken intraoperatively in the prevention of development of aseptic meningitis and concludes that total removal of epidermoids does not result in significantly increased morbidity and mortality and should be the goal of surgical treatment. However, near/subtotal resection of lesions that are densely adherent to neurovascular structures is justified, as there is no significant difference in the rate of recurrence. An endoscope can be used to assess the completeness of surgery.